Relationship between Diffuse CO2 Degassing and Volcanic Activity. Case Study of the Poás, Irazú, and Turrialba Volcanoes, Costa Rica - Epiard, Matthieu; Avard, Geoffroy; de Moor, J. Maarten; Martínez Cruz, María; Barrantes Castillo, Gustav; Bakkar, Henriette (Frontiers in Earth Science, 2017)
Active volcanoes exhibit diffuse gas emanations through the ground, the most abundant species of which is CO2. However, the relationship between diffuse degassing and volcanic activity is not often clear and some volcanoes may have low diffuse degassing levels despite having strong volcanic activity. The main goals of this study are to quantify diffuse CO2 degassing and determine whether patterns exist in relation to volcanic activity through the study of Turrialba, Poás and Irazú, three active volcanoes in Costa Rica which are at different stages of activity. Structural controls of spatial distribution of diffuse degassing were also investigated. Measurement campaigns were conducted using the accumulation chamber method coupled with 10 cm depth ground temperature sampling with the aim of estimating the total diffuse CO2 degassing budget. The total amount of CO2 emitted diffusely by each volcano is approximately 113 ± 46 t/d over ~ 0.705 km2 for Turrialba, 0.9 ± 0.5 t/d for Poás over ~ 0.734 km2, 3.8 ± 0.9 t/d over ~ 0.049 km2 for Irazú's main crater, and 15 ± 12 t/d over 0.0059 km2 for Irazú's north flank. Turrialba and Poás volcano diffuse degassing budget represent about 10% of the whole gas output. Both volcanoes were in a transitional stage and the opening of new conduits may cause a loss in diffuse degassing and an increase of active degassing. Numerous diffuse degassing structures were also identified. One of which at Turrialba was closely associated with the collapse of a crater wall in 2014 during the initiation of a new period of heightened eruptive activity. Similar structures were also observed on the outer slopes of the west crater, suggesting strong alteration and perhaps destabilization of the upper outer cone. Irazú's north flank is highly permeable and has experienced intense hydrothermal alteration.